Search for the optimal way in the network of public communication - Keršys, Artūras; Jurkauskas, Algirdas (Transport, 2002)
The problem of searching the optimal way in the network of public communication is investigated in the article. The modified Minieka algorithm and designed combined search into depth and Dijkstra algorithm method, operating by the basis of graphs are presented. In order to evaluate practically the efficiency and applicability of algorithms experimental calculating of route search in the model of public transport communication network has been made. Public transport network changed in to graph is a real public transport network segment in Kaunas. Having compared their efficiency (memory size and calculating time) it has been proved that both methods might be applied to solve the problem as well as be integrated into the prediction models of communication processes. The combined depth-first search and Dijkstra algorithm method are better. First Published Online: 19 Oct 2011